2000
DOI: 10.1207/s15327078in0104_3
|View full text |Cite
|
Sign up to set email alerts
|

Object Permanence in Five‐and‐a‐Half‐Month‐Old Infants?

Abstract: Event Set x Event Set designs were used to study the rotating screen paradigm introduced by Baillargeon, Spelke, and Wasserman (1985). In Experiment 1, 36 S%-month-old infants were habituated to a screen rotating 180" with no block, a screen rotating 120" up to a block, or a screen rotating 180" up to and seemingly through a block. All infants were then tested on the same 3 events and also a screen rotating 120" with no block. The results indicate that infants are using novelty and familiarity preference to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 22 publications
2
74
0
1
Order By: Relevance
“…Second, as was mentioned earlier, some researchers have suggested that infants tested with violation-of-expectation tasks involving hidden objects may look reliably longer at the unexpected than at the expected events, not because they can represent and reason about hidden objects, but because the familiarization or habituation trials induce in them transient preferences for the unexpected events (e.g. Bogartz et al, 2000;Cashon & Cohen, 2000;Roder et al, 2000;Schilling, 2000;Thelen & Smith, 1994). Evidence that infants also succeed in tasks with test trials only can help alleviate these concerns (for additional evidence and discussion, see Wang et al, 2004).…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Second, as was mentioned earlier, some researchers have suggested that infants tested with violation-of-expectation tasks involving hidden objects may look reliably longer at the unexpected than at the expected events, not because they can represent and reason about hidden objects, but because the familiarization or habituation trials induce in them transient preferences for the unexpected events (e.g. Bogartz et al, 2000;Cashon & Cohen, 2000;Roder et al, 2000;Schilling, 2000;Thelen & Smith, 1994). Evidence that infants also succeed in tasks with test trials only can help alleviate these concerns (for additional evidence and discussion, see Wang et al, 2004).…”
Section: Methodsmentioning
confidence: 93%
“…Bogartz, Shinskey, &Schilling, 2000;Bogartz, Shinskey,&Speaker, 1997;Cashon&Cohen, 2000;Rivera, Wakeley, & Langer, 1999;Roder, Bushnell, & Sasseville, 2000;Schilling, 2000;Thelen & Smith, 1994;see Wang et al, 2004, for discussion). Could the results of Experiment 1 be attributed to such preferences?…”
Section: 23mentioning
confidence: 99%
“…A number of researchers have argued that young infants may respond with increased attention to some events in VOE tasks, not because these events violate their physical knowledge, but because the habituation or familiarization trials induce in them transient and superficial preferences for the events (e.g. Bogartz, Shinskey, & Schilling, 2000;Bogartz et al, 1997;Cashon & Cohen, 2000;Cohen & Marks, 2002;Schilling, 2000). We refer to such accounts as transient-preference accounts (for a detailed discussion and test of such accounts, see Wang et al, 2004).…”
Section: Transient Preferences?mentioning
confidence: 99%
“…Diamond (1995) found that 6-month-old infants indeed have good recognition memory even in tasks that require reaching for the reward and attributed the failure to other factors, such as the inability to execute a means-end action sequence, relational skills, or speed of processing. Moreover, according to Bogartz, Shinskey, and Schilling (2000); Cashon and Cohen (2000); and Schilling (2000), infants do not use the possibility or impossibility of events but instead novelty and familiarity preference to determine their looking times. Rivera, Wakeley and Langer (1999) also questioned Baillargeon et al's (1985) claim that in their study the behavior of infants was due to representational reasoning but suggested rather that it is because of simple perceptual preferences.…”
mentioning
confidence: 99%